CANVA AS A DIGITAL LEARNING MEDIUM TO DEVELOP STUDENT CREATIVITY AT AL-AZHAR MEDAN HIGH SCHOOL - Ayla Arini Putri; Mhd. Rafif Zuhdi Matondang; Sunarji Harahap; Arya Fadillah Kesuma; Rizki Akbar Ramdana Aulia Putra; Celsi Olivia Daulay (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to describe the role of Canva as a digital learning medium in developing student creativity at the high school level. The background of this study is based on the educational needs in the digital era, which demands interactive and engaging learning that can foster 21st-century skills, especially creativity. The research method used was descriptive qualitative with 15 students from class XII of Al-Azhar Medan High School as subjects. Data were obtained through questionnaires and observations of creativity indicators, including learning motivation, originality, idea elaboration, flexibility of thinking, and cooperation. The results showed that the use of Canva had a positive impact on the development of student creativity. A total of 90% of students showed high levels of motivation, originality, idea elaboration, flexibility, and cooperation. Canva helps students express creative ideas through attractive visual designs and increases participation and collaboration in groups. The obstacles found were mainly related to internet access and initial understanding of Canva's features, but these can be overcome through teacher guidance and independent exploration. Overall, this study concludes that Canva is effective as a digital learning medium that can enhance creativity and learning motivation among high school students, and is relevant for application in the context of innovative learning based on the Merdeka Belajar (Freedom of Learning) curriculum and the Deep Learning Approach.